Nonstandard Were and the Nonstandard forms of the Preterite Negative of to be in Nineteenth Century New England Civil War Letters and Literary Dialect Portrayals - Pablé, Adrian; Dylewski, Radosław; Urbańska, Agnieszka (Studia Anglica Posnaniensia, 2010)
The present paper presents the preliminary results of the study of were in nonstandard positions as well as nonstandard preterit negative forms of to be in mid- and late nineteenth century New England folk speech. More specifically, the aim of the study is to investigate whether the grammatical feature at issue, deemed to have been confined to the Mid- and South Atlantic states in several scholarly publications, is also attested in the verbal repository of New Englanders of the mid- and late nineteenth century. The analysis relies mainly on the scrutiny of two types of primary sources: informal Civil War letters penned by less literate individuals, and fictional portrayals written by New England regionalists. The data retrieved from the inspected body of material confirms the presence of were/weren't/wa'n't (and other spellings) in nonstandard contexts, preponderantly in the literary dialect portrayals, whereas Civil War correspondence seems rather devoid of the traits at issue. As indicated above, the paper presents the preliminary results of the study: it is believed that an analysis of a bigger corpus of Civil War material, which is currently being compiled, might identify more instances of forms at issue in nonstandard environments.